STUDI TEKNIS PLTS ROOFTOP 3KWP FRAMELESS WITH ON-GRID SYSTEM DI LINGKUNGAN KORI NUANSA JIMBARAN - Wahyu Dewangga, I G.N.A.B Rama; Dwi Giriantari, Ida Ayu; Sukerayasa, I Wayan (Jurnal SPEKTRUM; Vol 8 No 4 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i04.p10, 2022)
Solar light is an environmentally friendly renewable energy. According to RUEN, Bali Province has a fairly large potential for solar light utilization, namely 1,254 MW with a target for PLTS development in 2025 of 8.62% or 108.2 MW of its total potential. Therefore, this research focuses on the utilization of PLTS Rooftop on-grid as an energy supply at Kori Nuansa Jimbaran's residence which explains the specifications of the installed PLTS materials and components, as well as the design of the PLTSinstallation in Rooftop terms of technical terms according to the requirements of PT. PLN (Persero). The method used is literature review, observation, data collection, data analysis and conclusions. The results showed that the total daily load calculation was 26,151 W/day and the total daily energy that could be generated from the calculation was 14.58 kWh/day with the measurement results at the research location of 13.4 kWh/day where there was a difference of 1.18 kWh caused by due to losses in the system. When viewed from the total daily load the PLTS system has not met the needs, but functionally the PLTS system is intended for daytime loads so that the needs are appropriate. Optimal inclination angle of 14.66calculation results areº however on measurementsusing a protractor tool obtained18º this because the angle of inclination of the solar panels follows the direction of the slope of the roof. The installed PLTS design has met the standards of the Minister of Energy and Mineral Resources No. 49 of 2018 and has received an Operational Worthiness Certificate (SLO) from PT. PLN (Persero).